PENGARUH CAMPURAN ABU TERBANG (FLY ASH) DAN ASAM FOSFAT TERHADAP DAYA DUKUNG TANAH LEMPUNG - Muhammad Reza Pratama; Okrobianus Hendri; M. Ikhwan Yani (Universitas Lambung Mangkurat, 2022)
Based on observations in the field, the village of Tanjung Sanggalang is dominated by clay soil. Construction on clay soil, if not handled properly, can affect the construction on clay and can accelerate damage after the construction is completed. The alternative used to improve clay soil to make it more stable is soil stabilization using a mixture of fly ash and phosphoric acid. The purpose of this study was to analyze the physical properties of the soil and to analyze the bearing capacity of the soil before adding fly ash (A.T.) with phosphoric acid (A.F) and adding fly ash (A.T.) with phosphoric acid (A.F). The percentage of mixture for fly ash ash is 7.5% and for phosphoric acid the percentage of mixture is 5%, 7.5%, 10%. Based on the results of the study, the variation of the mixture experiencing changes in the bearing capacity of the highest soil is clay with a mixture of A.T. 7.5% and A.F. 10% of the yield, fly ash and phosphoric acid can increase the bearing capacity of clay soil.